Sensory and motor axonal excitability testing in early diabetic neuropathy. Issue 7 (July 2021) - Kristensen, A.G.; Gylfadottir, S.; Itani, M.; Kuwabara, S.; Krøigård, T.; Khan, K.S.; Finnerup, N.B.; Andersen, H.; Jensen, T.S.; Sindrup, S.; Tankisi, H.
Highlights: Excitability testing with threshold tracking was performed in 111 type 2 diabetics with and without diabetic polyneuropathy and 60 controls. Changes in sensory and motor excitability in diabetic polyneuropathy were subtle, perhaps because of the relatively short disease duration. There were only weak correlations between the excitability parameters and clinical scores. Abstract: Objective: The aim of the present study was to gain insight into the pathophysiology of diabetic polyneuropathy (DPN) and examine the diagnostic value of sensory and motor axonal excitability testing. Methods: One hundred and eleven type 2 diabetics with and without DPN (disease duration: 6.36 ± 0.25 years) and 60 controls were included. All participants received a thorough clinical examination including Michigan Neuropathy Screening Instrument (MNSI) score, nerve conduction studies (NCS), and sensory and motor excitability tests. Patients were compared by the likelihood of neuropathy presence, ranging from no DPN (17), possible/probable DPN (46) to NCS-confirmed DPN (48). Results: Motor excitability tests showed differences in rheobase and depolarizing threshold electrotonus measures between NCS-confirmed DPN group and controls but no changes in hyperpolarising threshold electrotonus or recovery cycle parameters. Sensory excitability showed even less changes despite pronounced sensory NCS abnormalities. There were only weak correlations between the above motor excitability parameters and clinical scores. Conclusions: Changes in excitability in the examined patient group were subtle, perhaps because of the relatively short disease duration. Significance: Less pronounced excitability changes than NCS suggest that axonal excitability testing is not of diagnostic value for early DPN and does not provide information on the mechanisms.